Size fraction >150 μm determination of sediment core LV76-21 - Sergey A Gorbarenko; Ivan S Kirichenko; Olga Psheneva; Aleksandr A Bosin (PANGAEA, 2025)
Sediment for IRD determination was sampled from 1 cm-thick slices with steps of 2–4 cm through the core. Samples with a dry weight of approximately 10 g were wet sieved using a 150 μm and 63 μm sieves. Coarse fraction >150 μm was decarbonized using 10% HCl, washed using distilled water, and dried. The ratio of weight percentage for the decarbonized coarse fraction (150–2,000 μm) relative to the weight of the dried bulk sediment were used as IRD. This is consistent with the commonly used size fraction > 150 μm for delimiting IRD (Hemming, 2004). Data in the intervals of the visible tephra layers were excluded from the IRD record because this material was delivered into sediment through the atmosphere, rather than by ice and, therefore, is not IRD. Need to understand that the nearby Kamchatka peninsula is area of active volcanism. Therefore, the determined IRD values (wt % of decarbonated fraction 150-2,000 μm) may include as terrigenous particles as volcanic particles, which were earlier fallout of the land during explosive volcanic eruptions, captured by sea ice and icebergs from the coast and land and then transferred into core location by water currents.
In: Gorbarenko, SA et al. (2025): Results of analysis of sediment core LV76-21 from Detroit Seamount [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.954780